Lipid-lowering drug targets and lung related diseases: a Mendelian randomization study - Haifeng Yu; Xiaofei Zhang; Bian Wen; Shuo Hu; Bin Ni (All Life)
OBJECTIVES This genetics-based study aimed to evaluate the relationships of long-term lipid-lowering agents on lung-related diseases (LRD) outcomes. METHODS We extracted genetic variations of six drug target genes from a major genome-wide association study of low-density lipoprotein cholesterol (LDL-C) in individuals predominantly of European ancestry to represent the effects of LDL-C-lowering treatment. We conducted drug-targeted Mendelian randomization and utilized a range of outcomes to capture evidence of adverse side effects related to the inhibition of the gene. RESULTS Our study did not find any significant association between genetically proxied APOB, CETP, HMGCR, NPCIL, PCSK9, and LDLR inhibition (equivalent to a one standard deviation reduction in LDL-C) with the risk of Small Cell Lung Cancer, Non-Small Cell Lung Cancer, idiopathic pulmonary fibrosis, and Pneumonia (P > 0.05). However, long-term inhibition of NPC1L that mimics the use of statin drugs may have contradictory effects on pulmonary edema (OR = 0.508, 95%CI = 0.328–0.786,P = 0.002) and chronic obstructive pulmonary disease (OR = 1.524, 95%CI = 1.099–2.115, P = 0.012). A series of sensitivity analyses and positive control analyses have been conducted to confirm the reliability of the results. CONCLUSIONS In conclusion, this study reveals inconsistent associations between genetic proxy inhibition of APOB, CETP, HMGCR, NPCIL, PCSK9 and LDLR with LRD in specific populations.